Sweet and fatty symbionts: Photosynthetic productivity and carbon storage boosted in microalgae within a host - Andrea Catacora-Grundy; Caroline Juery; Fabien Chevalier; Daniel P. Yee; Marie Pavie; Charlotte LeKieffre; Nicole L. Schieber; Yannick Schwab; Benoit Gallet; Pierre Henri Jouneau; Gilles Curien; Johan Decelle (Proceedings of the National Academy of Sciences, 2026)
Symbiosis between a host and intracellular eukaryotic microalgae is a widespread life strategy in aquatic ecosystems. This partnership is considered to be mainly energized by the supply of photosynthetically derived carbon energy from microalgal symbionts. A major question is whether microalgae increase their photosynthetic production and decrease carbon storage in order to maximize carbon translocation to their host. By combining three-dimensional subcellular imaging and physiological analyses, we show that the chloroplast and CO 2 -fixing pyrenoid of the microalga Micractinium conductrix significantly expands during symbiosis within their host (the ciliate Paramecium bursaria ) compared to the free-living stage. This is accompanied by a threefold higher quantity of Rubisco enzymes, 16-fold higher carbon fixation rate per algal cell and upregulation of several Carbon Concentrating Mechanism-related genes. Time-resolved subcellular quantitative imaging revealed that photosynthetically fixed carbon is first allocated to starch during the day, with five times higher production in symbiosis. Nearly half of the carbon stored in starch is consumed overnight while some is converted into lipid droplets, which are 20-fold more voluminous in symbiotic microalgae. We also show that carbon is transferred to the host and potentially respired by the high density of surrounding host mitochondria. Yet, high starch and lipid content in symbiotic microalgae suggest a moderate carbon export to the host relative to the high primary productivity. Overall, this study provides an original view of the subcellular remodeling and dynamics of carbon metabolism of microalgae inside a host, and opens new questions on the mechanisms of the source–sink relationship in aquatic photosymbiosis.